Onde está Deus na ALCA? Deus luta conosco por uma negociação justa - Hernández Pico, Juan (Revista Eclesiástica Brasileira, 2003)
A ALCA, que pretende criar, sob a égide dos EUA, uma área de livre comércio nas Américas, implica num grave desafio para os países pobres da América Latina (AL) e do Caribe. J.H. Pico, Jesuíta venezuelano, analisa a ALCA dos pontos de vista ético e teológico. Na perspectiva ética se pergunta: a ALCA leva em conta o lado propriamente humano da integração econômica entre países ricos do Norte e pobres do Sul? Na ALCA, as vantagens não pendem só para o lado rico? Na ótica teológica se pergunta: a ALCA salvaguardará os direitos dos pobres? Respeitará as exigências da solidariedade e da fraternidade neste mundo, criado por Deus e confiado a seus filhos e filhas, para que todos possam chegar à vida em plenitude? Cabe aos cristãos lutar, sem desanimar, a fim de corrigir as graves distorções implícitas na ALCA. Abstract: The Free Trade Area of the Americas (FTAA), that, under the US patronage, intends to create a free trade area in the Americas, presupposes a serious challenge for the poor countries of Latin America and the Caribbean. J.H. Pico, a Venezuelan Jesuit, analyses the FTAAfrom an ethical and theological point of view. With regard to the ethical perspective, he asks: does the FTAAreally take into consideration the human aspect of the economic integration between the rich Northern countries and the poor Southern ones? Is it not the case that in the FTAA the advantages tend towards the rich side only? With regard to the theological viewpoint, he asks: will FTAA safeguard the poor countries’interest? Will it respect the demands for solidarity and fraternity in this world created by God and entrusted to His sons and daughters, so that all can achieve a plentiful life? It is up to the Christians to struggle unflaggingly to correct the serious distortions implicit in the FTAA.